IMPLEMENTASI HUKUM ISLAM DALAM PENETAPAN HAK ASUH ANAK PASCA PERCERAIAN DI INDONESIA - Nurfaika Ishak; Kurniati; Misbahuddin; Muammar M. Bakry; Abd. Rauf M. Amin (Universitas Islam Negeri Alauddin Makassar, 2025)
Child custody is one of the crucial aspects in divorce cases, often becoming a dispute between separating spouses. This study aims to analyze how Islamic law regulates child custody and how it is implemented in decisions of the Religious Court in Indonesia through a sociological approach. The research method used is library research, drawing from primary sources such as the Qur’an and Hadith, as well as various relevant scholarly works on child custody determination after divorce based on the enforcement and practice of Islamic law in Indonesia. The findings indicate that, in Islam, child custody is generally granted to the mother. However, its implementation in the Religious Court does not always follow this principle, as custody may also be awarded to the father based on specific considerations. Judges’ decisions regarding child custody take multiple factors into account, with the primary objective of safeguarding the child's best interests and well-being. As victims of divorce, children require protection, care, and affection from both parents to ensure proper growth and development while avoiding harmful psychological effects. Therefore, child custody determination is not solely based on normative texts but also considers the principle of child welfare (mashlahah al-thifl) as a fundamental guideline.